MANFAAT STANDARISASI KINERJA ANGKUTAN PERKOTAAN - Basuki, Imam (Jurnal Transportasi, 2008)
AbstractÂ Low quality of service in urban public transport results in the people preference to use private vehicles over the public transportation. This study tries to evaluate some performance standards implemented in some cities in the world. Based on this study, the standardization of urban transport performance for Indonesian cities is needed so that public transport service in those cities can be provided at optimum level. The standardization of public transportation service should address the needs of passenger, operator, regulator, and other users. In addition, the standardization has to consider sustainable environment and law enforcement as well.Keywords: standardization, urban transportation, performance